Parents’ Strategies In Improving Childrens’ Ability To Memorize Al Qur’an - Enna Juhana; Sri Nurhayati (Universitas Negeri Padang, 2023)
The purpose of this research was to analyze the parents’ strategies applied in improving childrens’ ability in memorizing Al Qur’an. The research method used in this study is qualitative with case study method, because this research describes or describes the state of the object under study in accordance with the facts as they are. The research data was taken from in depth interviews, observation and documentation study with several informants and the subjects of this research were 2 families (family of Mr A and family of Mrs. J). The place where the research process took place was in the Caringin Street 006/002, Margajaya Village, Ngamprah District, West Bandung Regency. The research found that the informants parents’ strategies in improving children’ ability to memorize the Qur’an include:1) parents must start to memorize Qur’an before the children, 2) give the children rewards everytime their reach the target, 3) register their children into tahfiz based school, 4) memorizing the Qur’an together with the children, 5)always send sincere prayers so Allah make it easy for the children to memorize the Qur’an, 6)make a regular tahfiz schedule daily.